2021
DOI: 10.1029/2020pa003946
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Water Formation in the North Pacific During the Late Miocene Global Cooling

Abstract: Intermediate-deep layers are well-ventilated in most modern oceans (Figure 1a), typically in the North Atlantic and Southern Oceans; this is primarily related to deep-water formation (Marshall & Speer, 2012; Weaver et al., 1999). This process plays a fundamental role in regulating global climate by affecting heat, gas exchange and nutrient cycles (Burls et al., 2017). In contrast, no new deep-water mass are formed in the modern North Pacific due to low-surface salinities and the existence of a strong halocline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 95 publications
(164 reference statements)
1
22
0
Order By: Relevance
“…This picture generally matches interpretations of drift sedimentation in the northeastern Atlantic (Uenzelmann-Neben & Gruetzner, 2019), but not in Newfoundland where sediment drifts suggest a later final intensification of NADW in the Pleistocene (Boyle et al, 2017). A focused study on North Pacific εNd suggests NPDW was being produced until 14 Ma, after which a southern source takes over (Kender et al, 2018), although see Zhai et al (2021) and Burls et al (2017). Holbourn et al (2013a)…”
Section: Deep Water Provenance From εNdsupporting
confidence: 58%
See 3 more Smart Citations
“…This picture generally matches interpretations of drift sedimentation in the northeastern Atlantic (Uenzelmann-Neben & Gruetzner, 2019), but not in Newfoundland where sediment drifts suggest a later final intensification of NADW in the Pleistocene (Boyle et al, 2017). A focused study on North Pacific εNd suggests NPDW was being produced until 14 Ma, after which a southern source takes over (Kender et al, 2018), although see Zhai et al (2021) and Burls et al (2017). Holbourn et al (2013a)…”
Section: Deep Water Provenance From εNdsupporting
confidence: 58%
“…It has also been suggested that the LMCIS was primarily the result of background biological overprinting due to changes in photosynthetic pathways in marine and terrestrial primary producers that influenced δ 13 C org and therefore δ 13 C DIC (Falkowski et al, 2005;Katz et al, 2005). Zhai et al (2021) add to this picture with the first geochemical evidence of the Biogenic Bloom in the Japan Sea.…”
Section: Evidence Of Changes In the Miocene Carbon Cyclementioning
confidence: 91%
See 2 more Smart Citations
“…Then, these pretreated sediments were digested by a concentrated HF + HNO 3 +HClO 4 mixture in Teflon vessels for the elemental analysis. The major and trace element concentrations were determined at the Institute of Oceanology, Chinese Academy of Sciences (IOCAS), Qingdao, using a Thermo Icap6300 ICP‐AES and a Perkin‐Elmer ELAN DRC II ICP‐MS, respectively (Zhai et al., 2021). Several USGS and Chinese rock and sediment standards (BCR‐2, BHVO‐2, GBW07315, and GBW07316) and blanks were repeatedly digested and analyzed in parallel with the samples to monitor the quality of measurements.…”
Section: Methodsmentioning
confidence: 99%